Penerapan Community Based Mitigation dalam Pengurangan Risiko Bencana Banjir Di Desa Lundo Kecamatan Benjeng Kabupaten Gresik - Umi Fauziyah; Arimurti Kriswibowo (JPG (Jurnal Pendidikan Geografi), 2023)
Disaster mitigation has the aim of reducing the impacts that arise, especially for local residents and increasing public understanding in dealing with the impacts and risks of disasters. The purpose of this study is to find out and explore the implementation of community based mitigation in reducing flood risk in Lundo Village, Benjeng District, Gresik Regency. The research method used descriptive qualitative with sampling technique using purposive sampling and snowball sampling. The results of the study can be concluded that the implementation of community-based mitigation has been carried out by Lundo Village. This is evidenced by the strengthening of community-based organizations with mutual cooperation efforts, the construction of embankments and the participation of energy and thoughts by the local community. Identifying needs and priorities by observing the conditions and the affected environment. Develop budget proposals for funds to be given to affected residents by collaborating with other organizations such as youth ansor. Encouraging participation with the aim of preventing excessive disaster risk by conducting socialization. Integrating mitigation with infrastructure development for disaster risk prevention